The Impact of Knowledge and Creativity in Architectural Design Studios: Architecture & Urban Planning Program at University of Tripoli Alahlia as A Case Study - Abtihal Ammar; Khairy Hassan (AlQalam Journal of Medical and Applied Sciences, 2024)
This paper focused on analyzing and exploring the role of knowledge in instilling and developing creativity within architectural design studios as an essential element of architectural education. It answered the question of the research problem: “How can the program present knowledge in a way that helps the student transform theoretical knowledge into practical practice and creativity in the architectural design studio?” It’s based on two scientific approaches: the inductive approach and the systems analysis approach and using the latest research findings in international research databases on the topics similar of this topic. The importance of this research paper lies in its contribution to solving the problems of architectural education. The research concluded a set of realistic, applicable results and succeeded in providing a vision and an integrated framework on the factors in the transformation of knowledge into practical practice and creativity, the policies and procedures of the educational program that support the transformation of theoretical knowledge presented to the student into practice and creativity, the practices that the studio professor must take into account to support the development of Motivation, ability to learn and creativity. The research recommended planning to implement its findings through developing policies, procedures, and practices for the educational program and the architectural design professorship. also recommended further studies to reveal the reality of implementing the research results practically in the architectural design studio in the architecture program within the University of Tripoli Alahlia (UTA) and architectural education programs in Libya. ركزت هذه الورقة البحثية على تحليل واستكشاف دور المعرفة في غرس وتنمية الإبداع داخل استوديوهات التصميم المعماري كعنصر أساسي في التعليم المعماري، وأجابت على تساؤل مشكلة البحث: "كيف يمكن للبرنامج تقديم المعرفة بطريقة تساعد الطالب على تحويل المعرفة النظرية إلى ممارسة عملية وإبداع في استوديو التصميم المعماري؟" وهي تستند إلى منهجين علميين: المنهج الاستقرائي ومنهج تحليل النظم واستخدام أحدث النتائج البحثية في قواعد البيانات البحثية العالمية حول مواضيع مشابهة لهذا الموضوع. تكمن أهمية هذه الورقة البحثية في مساهمتها في حل مشكلات التعليم المعماري، وخلص البحث إلى مجموعة من النتائج الواقعية القابلة للتطبيق ونجح في تقديم رؤية وإطار متكامل حول عوامل تحويل المعرفة إلى ممارسة عملية وإبداع، وسياسات وإجراءات البرنامج التعليمي التي تدعم تحويل المعرفة النظرية المقدمة للطالب إلى ممارسة وإبداع، والممارسات التي يجب على أستاذ الاستوديو مراعاتها لدعم تنمية الدافعية والقدرة على التعلم والإبداع. وأوصى البحث بالتخطيط لتنفيذ نتائجه من خلال تطوير السياسات والإجراءات والممارسات الخاصة بالبرنامج التعليمي وأستاذية التصميم المعماري، كما أوصى بإجراء المزيد من الدراسات لكشف واقع تطبيق نتائج البحث عمليا في استوديو التصميم المعماري في برنامج الهندسة المعمارية بجامعة طرابلس الأهلية وبرامج التعليم المعماري في ليبيا